2010
DOI: 10.1242/dmm.003681
|View full text |Cite
|
Sign up to set email alerts
|

Erlotinib resistance in mouse models of epidermal growth factor receptor-induced lung adenocarcinoma

Abstract: SUMMARY Seventy-five percent of lung adenocarcinomas with epidermal growth factor receptor (EGFR) mutations respond to treatment with the tyrosine kinase inhibitors (TKIs) gefitinib and erlotinib; however, drug-resistant tumors eventually emerge. In 60% of cases, resistant tumors carry a secondary mutation in EGFR (T790M), amplification of MET, or both. Here, we describe the establishment of erlotinib resistance in lung tumors, which were induced by mutant EGFR, in transgenic mice after multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 21 publications
(28 reference statements)
2
77
0
2
Order By: Relevance
“…Cells were grown in a humidified incubator with 5% CO 2 at 37°C. To create EGFR TKIresistant lines, parental cells were cultured with increasing concentrations of TKIs starting with the IC 30 . Doses were increased in a stepwise pattern when normal cell proliferation patterns resumed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were grown in a humidified incubator with 5% CO 2 at 37°C. To create EGFR TKIresistant lines, parental cells were cultured with increasing concentrations of TKIs starting with the IC 30 . Doses were increased in a stepwise pattern when normal cell proliferation patterns resumed.…”
Section: Methodsmentioning
confidence: 99%
“…Given the RAS-related findings in the murine (30) and cell-line models of acquired resistance and the reported data regarding KRAS/NRAS/BRAF/MEK1 mutations in other cancers that grow after responding to targeted therapies (25-28), we reexamined the frequency of mutations occurring in KRAS, NRAS, BRAF, and MEK1 in 195, 212, 195, and 146 tumor samples, respectively, from patients with acquired resistance to EGFR TKIs. Tumors were screened by a variety of methods including a SNapShot/sizing platform (32,38), a Sequenom mass spectrometrybased assay (39), and/or direct sequencing.…”
Section: Ras Signaling Pathway Gene Mutations In Tumors From Patientsmentioning
confidence: 99%
“…To simulate tumor subclonal heterogeneity and contamination with infiltrating nontumor stromal cells, we serially diluted the 129S1/ SvImJ library (mimicking "tumor DNA") into the C57BL/6 library (10). Tumors were collected from untreated tumor-bearing mice, or mice were treated with erlotinib as described until the appearance of resistant tumors (12). Untreated and erlotinibresistant lung tumors were collected and used for exome sequencing.…”
Section: Mouse Models Of Lung Adenocarcinoma Acquire Few Somatic Pointmentioning
confidence: 99%
“…Thus, GEMMs, with their ability to mimic therapeutic resistance in toto and increased tumor tissue accessibility, could provide an invaluable means to model therapeutic response, refractory patient populations, and the dynamic evolution of tumors on treatment. An excellent example of GEMMs applied in this fashion is found in the work of Politi and colleagues (45), who showed that mouse models of mutant EGFR-driven lung carcinomas give rise to drug-resistant tumors that exhibit the same molecular changes that confer resistance in human lung cancers when treated with the tyrosine kinase inhibitor erlotinib. Similarly, GEMMs have been successfully used to model acquired resistance to chemotherapy and have provided key insights into the underlying mechanisms and cell types involved.…”
Section: Introductionmentioning
confidence: 99%